To What Extent Are Websites Used to Segment Target Users: A Website Effectiveness Study - Mudge, Timothy Robert (2007)
With the advent of computer and the Internet, came a new media to be exploited my marketing and advertising executives all over the globe. In its early years, Web sites were primitive and not used as a tool for branding. However, branding is everything and everywhere. The cars we drive, the food we eat, even our most mundane purchases like soap and toilet paper are clearly branded. But what comes to mind when we think of the elements of branding? Most immediately, we might think of packaging labels, bags, boxes, and the logos printed, stamped, or otherwise emblazoned upon them (Andres, 2002). However, these elements do no define a brand in today's ever-changing world.